2018
DOI: 10.1111/icad.12327
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of regional and local diversity of Amazonian stream Odonata

Abstract: Large Amazonian rivers may act as dispersal barriers for animals with low dispersal abilities, limiting their distribution to certain interfluves. Consequently, the distribution of these taxa would be less affected by macroclimatic gradients. Conversely, high‐dispersal taxa would be less constrained by large rivers and may track suitable climates. We evaluate whether Zygoptera and Anisoptera, two Odonata suborders with different dispersal abilities, show differences in distribution patterns across Amazonian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 76 publications
(97 reference statements)
2
19
0
Order By: Relevance
“…The composition of Odonata metacommunities across interfluves in Amazonia emerges mainly from a combination of Amazonian major rivers, macroclimate and habitat integrity environment (and space, in the case of Anisoptera) in Amazonia. These findings are consistent with previous studies showing that Amazonian biogeography (Juen & Marco, 2012; Brasil et al, 2017; Alves-Martins et al, 2018) and climate are the main drivers for Odonata metacommunities at coarser spatial scales (Chovanec et al, 2015; Bried et al, 2015). Our results also confirm that intactness of riparian forest is important for Amazonian stream Odonata communities (De Marco, Batista & Cabette, 2015; De Marco et al., 2015; Miguel et al, 2017; Alves-Martins et al, 2018) and distinct Amazonian districts show distinct community composition, which has important implication for conservation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The composition of Odonata metacommunities across interfluves in Amazonia emerges mainly from a combination of Amazonian major rivers, macroclimate and habitat integrity environment (and space, in the case of Anisoptera) in Amazonia. These findings are consistent with previous studies showing that Amazonian biogeography (Juen & Marco, 2012; Brasil et al, 2017; Alves-Martins et al, 2018) and climate are the main drivers for Odonata metacommunities at coarser spatial scales (Chovanec et al, 2015; Bried et al, 2015). Our results also confirm that intactness of riparian forest is important for Amazonian stream Odonata communities (De Marco, Batista & Cabette, 2015; De Marco et al., 2015; Miguel et al, 2017; Alves-Martins et al, 2018) and distinct Amazonian districts show distinct community composition, which has important implication for conservation.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the results of Brasil et al (2017), who found a Clementsian pattern for Zygoptera metacommunities in non-impacted streams at Belém and Tapajós interfluves, and Alves-Martins et al (2018), who found distinct species compositions across the interfluves of major Amazonian rivers. These results suggest that the Clementsian pattern in Amazonian Odonata may be related to the historical isolation of communities generated by the emergence of large rivers, which means that the edges of Odonata species ranges coincide with the limits of the interfluves (Juen & De Marco, 2012; Brasil et al, 2017; Alves-Martins et al, 2018). These distribution patterns follow the predictions of the theory of isolation by rivers in Amazonia, initially proposed by Wallace (1852), and that has been corroborated for other organisms (e.g., Cracraft, 1985; Bates, Haffer & Grismer, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Richness was not associated with the different spatial efforts employed, with no increase in richness as the area of sampled transects increased. Dragonflies are flying organisms with a high dispersal ability [ 10 ]. Perhaps the difference between 100, 200 and 300 meters is not enough to capture the change in species richness due to the easy dispersion of these insects along the stream, making it expensive to sample spaces larger than 100 meters.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we investigated the relationship between dung beetle body size, perch height and other plant traits in a tropical forest. We evaluated potential perching preferences and dung beetle-plant networks following similar approaches to those used for other tropical arthropods by de de Araújo and Daud (2018) and Alves-Martins et al (2019). Our research questions were: Do large beetles perch on higher plants than smaller beetles?…”
Section: Introductionmentioning
confidence: 99%